180° hybrid using a novel planar balun on suspended substrate for beam forming network applications. Issue 9 (19th May 2020) - Moghaddam, Elham S.; Ahmadi, Arash
Abstract: In this paper, a 180° hybrid consisting of a broadband balun and a T‐junction in‐phase power divider is proposed. The 180° hybrid is intended for operation in the C‐band. The balun resembles a center tapped magnetic transformer where the coils are replaced by broadside‐coupled lines. This new technique allows magnetic couplers to be realized by planar structures at microwave frequencies. The planar balun is broadband, and the size reduction is considerable. The broadside‐coupled lines are on a suspended substrate. The proposed structure can be used in the beam forming networks of the multiple‐beam antennas. It also prevents cross connections in the conventional beam forming networks. The planar balun is analyzed by the signal flow graph method. The scattering parameters of the 180° hybrid are calculated by the multiport connection method. Some design formulas for the construction of the balun are presented. The 3‐dimensional model of the planar 180° hybrid is simulated by a full‐wave simulator. Measurement results of the fabricated hybrid approve the simulation results. The 180° hybrid exhibits a relative bandwidth of 45% centered at 4.5 GHz. In the operating band, the amplitude and phase imbalance of the output ports are <0.6 dB and <10°, respectively.